Overview of the hybrid solar system - Al-Ktranee Mohammed (Analecta technica Szegedinensia, 2020)
This paper investigates the uses of solar energy systems in various applications to define the most appropriate system that has highly efficient and reliable. Most of the urban even rural areas that suffer from lack of continuous power supplies it prefers to depend on hybrid systems like solar/wind systems, solar/geothermal system, and solar/diesel-battery systems. Investigation indicates that hybrid systems could meet the required loads in different proportions depending on the operating conditions and components of the hybrid system compare with the separate system but has complexity regarding their components of the system with the high initial cost. Moreover, utilize hybrid solar/thermal system is more sufficient than had systems that mentioned as a result of the improvements at his parts to increase the overall efficiency by using phase change material (PCM), nanofluid or a mix of PCM - nanofluid as cooling the photovoltaic (PV) panel to keep the efficiency of the solar cells and increase thermal energy. Thus, hybrid solar/thermal systems had proven effective to meet the required loads of electric energy and good capacity to provide thermal energy simultaneously without toxic emissions with a negligible complexity of its components.